The Tarantula Scientist - Montgomery, Sy; Bishop, Nic (Boston : Houghton Mifflin Co., 2004)
Describes the research that Samuel Marshall and his students are doing on tarantulas, including the largest spider on earth, the Goliath birdeating tarantula.
Includes bibliographical references (p. 79) and index.
Keywords: Marshall, Samuel D -- Juvenile literature; Marshall, Samuel D; Tarantulas -- Juvenile literature; Tarantulas -- Juvenile literature. -- Research; Arachnologists -- Juvenile literature. -- United States; Tarantulas; Spiders; Arachnologists; Scientists